2009
DOI: 10.1080/08916930802282651
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and molecular characterization of regulatory T cells in connective tissue diseases

Abstract: The aim of our study was to investigate and characterize regulatory T cells (Treg) in peripheral blood of patients with connective tissue diseases (Systemic lupus erythematosus, systemic sclerosis, Sjögren's syndrome, poly- and dermatomyositis) as compared with blood from healthy controls. Treg cells were quantified and phenotypically characterized by flow cytometry while the expression level of Foxp3 mRNA was evaluated by real time PCR. A reduced percentage of peripheral blood Treg cells was found in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 54 publications
5
53
0
Order By: Relevance
“…2,7 The various Treg cells have key roles in maintaining self-tolerance and modulating the allergic and autoimmune responses, while controlling autoreactive T cells. [8][9][10][11] Several studies have reported a deficiency in the number of Treg and/or function in autoimmune disease patients, 12,13 namely in systemic lupus erythematous, 14 rheumatoid arthritis, 15 multiple sclerosis, 16 autoimmune polyglandular syndrome II, 17 myasthenia gravis 18 and type I diabetes. 19 However, results concerning the number of circulating Treg cells and their suppressive function have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7 The various Treg cells have key roles in maintaining self-tolerance and modulating the allergic and autoimmune responses, while controlling autoreactive T cells. [8][9][10][11] Several studies have reported a deficiency in the number of Treg and/or function in autoimmune disease patients, 12,13 namely in systemic lupus erythematous, 14 rheumatoid arthritis, 15 multiple sclerosis, 16 autoimmune polyglandular syndrome II, 17 myasthenia gravis 18 and type I diabetes. 19 However, results concerning the number of circulating Treg cells and their suppressive function have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In SSc patients, few studies investigated the various Treg subsets and their suppressive function, these also with conflicting results, showing either reduced, 20-22 increased 23,24 or the same [25][26][27] number of circulating Treg cells in peripheral blood as compared with controls. These discrepancies might be mostly due to variations in study techniques, with setting analysis of either CD4 þ CD25 þ , 21,23 CD4 þ CD25 high , 12,25,26 20,24,26 CD25 þ Foxp3 þ CD127 -23 or CD4 þ CD25 high CD127 low subsets. 22 Despite these controversies, in most of these studies of SSc patients' samples, 22,23,26 impaired Treg-suppressive function was associated with SSc disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmarks of the disease are inflammatory processes, dominantly in the skin and visceral organs, such as the heart, lungs, or kidneys [52,53]. The key role of the innate and adaptive immune system has been depicted in the pathogenesis of SSc [54][55][56][57]. Disorders of the immune system lead to chronic inflammatory processes, abnormal T cell activation, B cell abnormalities, abundant production of proinflammatory cytokines (e.g.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…Regulatory cells with impaired function have been shown to play a role in the initiation and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 perpetuation of the disease [56,57]. In SSc patients increased levels of circulating Th17 cell have been described, along with elevated IL-17 serum concentrations [58,59].…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…A study has investigated and characterized the number of T reg cells in the peripheral blood of patients with DM and compared results with other connective tissue diseases such as SLE, systemic sclerosis, and Sjögren's syndrome as well as healthy controls. A reduced percentage of peripheral blood T reg cells was found in patients compared to controls, irrespective of the type of connective tissue disease [98]. Antiga et al [99] investigated the frequency of CD4+CD25+ T reg cells in peripheral blood and their main effector cytokines in skin lesions and in serum from patients with DM and compared the results with cutaneous lupus erythematosus, psoriasis, atopic dermatitis and healthy controls.…”
Section: Treg and Autoimmune Diseasesmentioning
confidence: 99%